COMPARISON OF GENES EXPRESSION; MIRNA 146 A, MIR-103, MIR-423-3P, MIR-21, MIR-16 IN CELL LINES HEP-G2 SERIES 1886 AND PLC5 - Sukohar, Asep; Herawati, Hening; Witarto, Arief B; Sibero, Hendra T; ., Sutyarso (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Detection of hepatocellular cancer cells(HCC) in vitro has reached the smallest level, that is miRNA(micro RNA) in particular miRNA146A. This study was conducted from February to May2013 at the Department of Molecular Biology, Dharmais Cancer Hospital. The purpose of this study was to compare the value of Cq and expression ofmicroRNA(miRNA/mir) on Hep-G2 and PLC5. Methods: In vitro study were performed in Hep-G2 series 1886 and PLC5. The study used on 33 samples consisting of 5 groups of mir (miRNA146A, miR-423-3p, miR-103, miR-21and miR-16) in Hep-G2 and 5 groups of mirinPLC5 with 3 times repetition, 1 NTC and 2 spike. Results: MiRNA146 A expressionin Hep-G2against mir-423-3p, mir-103, mir-21, mir-16resulted in values as follows in consecutive order: (0.05), (0.03), (0.01), and (0.55). The highest expression was: miRNA146 Aagainst mir-16 and the smallest expression miRNA146 Aagainst mir-21in Hep-G2. MiRNA146 A expressionincell linesPLC5against mir-423-3p, mir-103, mir-21, mir-16resulted in values as follows: (0.01), (0.00), (0.00), and(0.02). The highest expression: miRNA146 A against mir-16, and the smallest expression: miRNA146 Aagainstmir-103 and mir-21 in PLC5. Conclusion: MiRNA 146 A, mir-423-3p, mir-103, mir-21, and mir-16 were expressed in Hep-G2 series 1886 and PLC5. The highest gene expression in miRNA146 A against mir-16 was found inHep-G2 andPLC5. The lowest gene expression in miRNA 146 A against mir-103 andmir-16 was found in PLC5. Keyword: Cell lines Hep-G2, miRNA 146 A, mir-423-3p, mir-103, mir-21, mir-16, PLC5.